The Role of the Principal in Era 4.0 in Improving School Quality through Democratic Leadership at Santa Lucia Kindergarten Medan - Saloma Banjarnahor; Nathanael Sitanggang; Wildansyah Lubis; Rosnelli Rosnelli (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This study aims to determine the role/relationship of the Principal in Era 4.0 in improving school quality through democratic leadership at Santa Lucia Kindergarten located in the Medan region. The population and sample in this study amounted to 130 students with a sample of 56 people. The data collection method in this study was a questionnaire or questionnaire. The data analysis technique used was simple linear regression analysis, t test and determination test. The conclusion is that school principals in Era 4.0 have a positive and significant effect/relationship on democratic leadership, school principals in Era 4.0 have a positive and significant effect/relationship on improving school quality, democratic leadership has a positive and significant effect/relationship on improving school quality, school principals in Era 4.